Improving Student’s Writing Skill through Mind Mapping - Berminati, Desi; Subari, Imam; Wiratno, Purna; Marcela, Eny Dwi (STKIP PGRI Bandar Lampung, 2023)
This research was aimed to improve students’ writing skill through mind mapping at the seventh grade of MTs Negeri 2 Bandar Lampung. The subject of this research consisted of thirty which consisted of 11 males and 19 females. This research was conducted by using classroom action research. Kemmis and Taggart stated about the model of action research it consisted of two cycles. Each cycle consisted of four steps; planning, action, observing, and reflecting. The writer did pre-cycle before going to cycle 1, the pre-cycle was conducted to know the students’ writing skill and the student difficulties in writing. In this research, the writer collaborated with the English teacher at the seventh (VII A) grade of MTs Negeri 2 Bandar Lampung to carry out the data of the students. At this research the writer was focused to improve the students’ learning activities and the students’ writing skill. The students’ improvement in learning activities it could be seen from the average score of students’ learning activities of cycle 1 were 7.16 with the criteria quite active, while in the second cycle that 7.87 was active. So, during the cycle 1 and the cycle 2 there were improvement of students’ learning activity, which got 0.71 point. Meanwhile in the students’ writing ability, the improvement could be seen from the average score of pre-cycle was 64.03 there were 17 students that passed the Minimum Mastery Criterion. Then the average score of first cycle was 69.03, there were 20 students or 66.66% who passed the Minimum Mastery Criterion and the average score of second cycle was 78.36 there were 25 students who passed the Minimum Mastery Criterion or 83.33%. Based on the result of analyzing the data it could be concluded that the Classroom Action Research through mind mapping can improve students’ learning activities and the students’ writing ability.